2001
DOI: 10.1159/000055689
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Multiple Cytokines and Inducible Nitric Oxide Synthase in Experimental Melanin-Protein-Induced Uveitis

Abstract: We investigated the kinetics of multiple cytokines and inducible nitric oxide synthase (iNOS) in experimental uveitis induced by bovine melanin protein (BMP) for the proper treatment of uveitis. Experimental uveitis was induced in male Lewis rats by injection of BMP. The levels of various inflammatory cytokines and iNOS mRNAs were semiquantified by the reverse-transcriptase reaction followed by PCR. The uveitis was started to develop at approximately day 14 and peaked around 21 days after immunization. The sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…34 Previous studies have demonstrated that EAAU is related to an elevation of inflammatory Th1 cytokines in uveitic eyes, whereas the Th2 cytokines increase at disease resolution. [9][10][11] In this study, after systemic Il-10 gene therapy, we demonstrated a significant decrease in the Th1 cytokine, TNF-␣, in combination with a rise in the Th2 cytokine, IL-10, in drainage lymph nodes during the initial stage of the disease. These results indicated that the elevation of sera IL-10 achieved by systemic Ad-IL-10 administration, but not by local injection, may alter Th2/Th1 balance by orienting the immune response toward a Th2-type cytokine profile in the peripheral lymphoid system, leading to, and subsequently eliminating, ocular inflammation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…34 Previous studies have demonstrated that EAAU is related to an elevation of inflammatory Th1 cytokines in uveitic eyes, whereas the Th2 cytokines increase at disease resolution. [9][10][11] In this study, after systemic Il-10 gene therapy, we demonstrated a significant decrease in the Th1 cytokine, TNF-␣, in combination with a rise in the Th2 cytokine, IL-10, in drainage lymph nodes during the initial stage of the disease. These results indicated that the elevation of sera IL-10 achieved by systemic Ad-IL-10 administration, but not by local injection, may alter Th2/Th1 balance by orienting the immune response toward a Th2-type cytokine profile in the peripheral lymphoid system, leading to, and subsequently eliminating, ocular inflammation.…”
Section: Discussionmentioning
confidence: 57%
“…8 Proinflammatory cytokines and chemokines function in selective leukocyte recruitment and, thus, play important roles in the pathogenesis of EAAU. [9][10][11] Specifically, a predominant Th1-type immune response has been identified based on the distinct cytokine profile detected in the iris/ciliary body in EAAU. 12 Because Th2 cells can downregulate Th1 cells and direct the immune response in a Th2 direction, Th2-cell-mediated immune reactions may have protective effects against ocular inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple cytokines have been studied in relation to EMIU, including: tumor necrosis factor (TNF)-␣ , interleukin (IL)-1 ␣ , IL-2, IL-4, IL-6, IL-10, IL-12, interferon-␥ and transforming growth factor-␤ [19][20][21][22] . The results are conflicting for some cytokines, but the evidence is strong that TNF-␣ participates in the initiation of EMIU, although the cell source is not defined.…”
Section: Molecular Mediatorsmentioning
confidence: 99%